Efektivitas Media Flashcard terhadap Kemampuan Membaca Siswa Sekolah Dasar: Sebuah Kajian Literatur - Haryadi; Bernadus Wahyudi Joko Santoso; Setiani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2026)
This literature review aims to analyze the effectiveness of flashcard media in improving elementary school students’ reading abilities between 2021 and 2025. Using the PRISMA systematic review framework, 168 relevant articles were selected and synthesized from Google Scholar and Crossref databases. The findings consistently demonstrate that flashcards are effective in enhancing early reading skills, particularly letter recognition, decoding, fluency, and reading motivation. Flashcards provide a dual visual-verbal stimulus that strengthens the association between form, sound, and meaning. Supporting factors include structured teaching design, teacher competence, sufficient practice frequency, and digital media integration, while limitations involve small samples, short intervention durations, and limited experimental controls. Compared with digital or game-based media, flashcards are simpler and effective for foundational reading, though digital media offer higher motivation and retention. Future studies should adopt stronger experimental designs and explore long-term comprehension effects. This review highlights the strategic role of flashcards in early literacy instruction and offers insights for teachers and educational researchers. Keywords: Lashcard media; reading skill; elementary students.